Changes in maximal oxygen uptake during growth and development in girls who actively participate in basketball and non-athletes girls: a longitudinal study - Stojmenović, Tamara; Ćurčić, Djordje; Vukašinović-Vesić, Milica; Andjelković, Marija; Dikić, Nenad; Kostić - Vučićević, Marija; Baralić, Ivana; Jakovljević, Vladimir; Živković, Vladimir (Vojnosanitetski pregled, 2020)
Background/Aim. It is well known that continuous engagement in physical activity is important for normal growth and development of children. Maximal oxygen uptake (VO2max), as a measure of functional state of the organism, is largely affected by level of physical activity, but it remains unclear to what extent it can be improved during childhood. The aim of the study was to evaluate dynamics of changes in aerobic capacity, anthropometric and body composition characteristics in active and non-active girls over a period of 3 years. Methods. A total of 48 young girls were included in the study. Girls were divided into 2 groups: training group consisted of 25 girls who played basketball (age 13.84 ± 0.94) and non-training group of 23 girls who were not involved in any organized sports (age 13.83 ± 0.98). Anthropometric and body composition characteristics were measured in order to monitor somatic growth during the study. VO2maxvalues were obtained by performing cardiopulmonary exercise testing on a treadmill. All parameters were measured every 6 months during 3-years period. Results. ANOVA analysis showed a significant time and group interaction effect on VO2max (p < 0.001), body mass index (BMI) (p < 0.001) and fat percentage (FAT%) (p < 0.01). Also, there was an obvious increase in VO2max within both groups due to growth and development itself (p < 0.001). Conclusion. The main finding of the study was an increase in VO2max due to growth and development. The girls who actively participated in basketball had higher level of aerobic capacity compared to non-active girls. Furthermore, continuous basketball training led to maintaining normal body composition in terms of FAT% and BMI, which altogether may imply that organized physical activity has a positive influence on evaluated characteristics.
Keywords: exercise; oxygen consumption; growth and development; basketball; adolescent; women.